Narrowing the climate information usability gap - and Lemos, Maria Carmen; Kirchhoff, Christine J.; Ramprasad, Vijay (Nature Climate Change, 2012)
Climate-change-related risks pose serious threats to the management of a wide range of social, economic and ecological systems. Managing these risks requires knowledge-intensive adaptive management and policy-making actively informed by scientific knowledge, especially climate science1. However, potentially useful climate information often goes unused1,2. This suggests a gap between what scientists understand as useful information and what users recognize as usable in their decision-making. We propose a dynamic conceptual model to address this gap and highlight strategies to move information from useful to usable to reduce climate-related risks.